2011
DOI: 10.1590/s1516-05722011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of extracts from Brazilian Cerrado plants on Colletotrichum gloeosporioides and Corynespora cassiicola

Abstract: This study aimed to determine the antifungal activity of leaf aqueous and hydroethanolic extracts of 10 plants from the Brazilian Cerrado on Colletotrichum gloeosporioides and Corynespora cassiicola. Antifungal activity was measured through the incorporation of each extract in a culture media or spore suspension, at 50% concentration relative to the volume, determining respectively the mycelial growth and the spore germination. Then, the percentages of mycelial growth inhibition and spore germination inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…On the other hand, methanolic extracts of leaves of M. splendens did not exhibit any inhibitory activity in Candida albicans and Cryptococcus neoformans (Scio et al, 2012). In a research on the antifungal activity of aqueous and hydroethanolic extracts of Cerrado species, Naruzawa and Papa (2011) observed that extracts of Aristolochia esperanzae and Byrsonima verbascifolia stimulated the growth of the phytopathogenic fungus Corynespora cassiicola, while extracts of Lafoensia pacari and Myracrodruon urundeuva inhibited 100% of the mycelial growth of the same fungus.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, methanolic extracts of leaves of M. splendens did not exhibit any inhibitory activity in Candida albicans and Cryptococcus neoformans (Scio et al, 2012). In a research on the antifungal activity of aqueous and hydroethanolic extracts of Cerrado species, Naruzawa and Papa (2011) observed that extracts of Aristolochia esperanzae and Byrsonima verbascifolia stimulated the growth of the phytopathogenic fungus Corynespora cassiicola, while extracts of Lafoensia pacari and Myracrodruon urundeuva inhibited 100% of the mycelial growth of the same fungus.…”
Section: Resultsmentioning
confidence: 99%
“…Those in vivo tests as well as their phitochemical analysis allows to evaluate some mechanism evolved in the control of micro-organisms that are plant pathogenic, whose in many times can remain alive in in vivo conditions as related by Rodrigues et al (2007), using ginger (Zingiber officinalis Roscoe) crude extract applied to lettuce leaves, reducing mycelial growth of S. sclerotiorum in 93%, There are few studies using B. crassifolia extracts in plant pathogens, however Guilhon-Simplicio and Pereira (2011) pointed antifungal properties of the bark, leaves, flowers, fruits and roots of this specie in several pathogens that affect human health. Naruzawa and Papa (2011) observed that the hydro ethanol extract from barks of B. verbascifolia Rich ex. Juss had antifungal activity, affecting mycelial growth and spore germination of Corynespora cassiicola (Berk.…”
Section: Resultsmentioning
confidence: 99%
“…The total inhibition of the mycelial growth occurred at the concentration of 8% of In general, the extracts with ethanol as solvent proportioned a higher inhibition of mycelial growth. According to Naruzawa and Papa [20], hydroethanolic extracts were more efficient at inhibiting both mycelial growth and spore germination. For the authors, ethanol is a better extractor of substances with antifungal characteristics.…”
Section: Effect In Vitro Of the Extracts Upon The Mycelial Growth Andmentioning
confidence: 99%